Mesenchymal stem cell therapy for injured growth plate - Awang, Mohd Shukrimi; Mohd, Afizah; Jacqueline F , Schmitt; James, Hui (Frontiers in Bioscience, 2013)
The growth plate has a limited self-healing capacity. Fractures sustained to the growth plate of young children could cause growth disturbances like angular deformity or growth arrest. Established therapies for injured physis only address related complications. Mesenchymal stem cells (MSCs) are multipotent cells which are capable of differentiating into various cells of the musculoskeletal system. Various MSC types have been tested for physeal regeneration, through in vivo lapine, porcine and ovine models, for the duration of 4-16 weeks. The created defect sizes ranged from 7-50% of the growth plate area, to simulate clinically-encountered cases. In vitro models have also been investigated, as a means to screen potential treatments. The effects of MSCs gathered from these models have revealed its function in the prevention of bone bridge formation, with the subsequent development of organized physeal repair tissue. Possible influential factors like the number of implanted MSCs, preconditioned state, growth factors, chondrocyte-MSC interaction and scaffolds are discussed. Possible further studies to optimize physeal repair based on MSC therapy in articular cartilage are also included.